2022
DOI: 10.1021/acsnano.2c07251
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane Curvature Modulated Lipopeptide to Broadly Combat Multidrug-Resistant Bacterial Pneumonia with Low Resistance Risk

Abstract: The extensive spread of multidrug resistance to Gram-negative bacteria has become a huge threat to human health, where peptide-based antibacterial agents have emerged as a powerful star weapon. Here we report a lipopeptide (LP-20) constructed nanomicelle with a different antibacterial mechanism of membrane curvature modulation, which induced dynamic membrane fission resulting in acceleration and enhancement of antibacterial activity to clinically isolated ESKAPE strains, including multidrug-resistant (MDR) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…22 These experimental findings, combined with our simulations and energybased theoretical analyses, aid in comprehending the mechanism behind recently observed MAP-induced morphological changes in live cells. 17,21,22 Our work clearly demonstrates that the simplistic membrane models utilized in previous studies are inadequate for simulating MAP activity, as certain behaviors such as changes in membrane curvature may be easily overlooked. These findings have significant implications for enhancing the biological efficacy of MAPs while minimizing their cytotoxicity through adjustments to their membrane-dependent attack mode.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…22 These experimental findings, combined with our simulations and energybased theoretical analyses, aid in comprehending the mechanism behind recently observed MAP-induced morphological changes in live cells. 17,21,22 Our work clearly demonstrates that the simplistic membrane models utilized in previous studies are inadequate for simulating MAP activity, as certain behaviors such as changes in membrane curvature may be easily overlooked. These findings have significant implications for enhancing the biological efficacy of MAPs while minimizing their cytotoxicity through adjustments to their membrane-dependent attack mode.…”
mentioning
confidence: 60%
“…76 The recent experiments conducted by Zou et al have demonstrated that peptide-induced membrane fission can also contribute to membrane damage. 22 These findings suggest that the leakage of contents and cellular death in bacteria under the influence of MAPs may not be solely attributed to pore formation. Classical models of pore formation primarily focus on the poration effect of peptides, while complex interactions between peptides and lipids are often overlooked.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Extended-spectrum β-lactamases (ESBL) and methicillin-resistant Staphylococcus aureus (MRSA) are multidrug-resistant bacterial pathogens with strong infectivity and high lethality. 23 The minimal inhibitory concentration (MIC) of Pep 6 against MRSA DN65 and ESBL T1T was 25 and 20.88 ± 7.21 μg/mL, respectively. In contrast, TPA showed no notable antimicrobial activity, with MIC values above 400 μg/mL (Table S1).…”
Section: ■ Resultsmentioning
confidence: 97%
“…The bioactivity of Hydrogel-RL was measured against the increasing emergence and dissemination of resistant bacterial pathogens. Extended-spectrum β-lactamases (ESBL) and methicillin-resistant Staphylococcus aureus (MRSA) are multidrug-resistant bacterial pathogens with strong infectivity and high lethality . The minimal inhibitory concentration (MIC) of Pep 6 against MRSA DN65 and ESBL T1T was 25 and 20.88 ± 7.21 μg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%